Zero-field atomic magnetometer to extract longitudinal magnetic field - Shuying Wang; Jixi Lu; Kaixuan Zhang; Le Zhao; Yibo Qi; Jiancheng Fang (Physical Review Research, 2025)
Zero-field atomic ensembles enable the development of ultrahigh-sensitivity magnetometry. However, their intrinsic insensitivity to longitudinal magnetic fields along the pumping direction poses a fundamental limitation, restricting precise weak-field quantification and complex system decoupling. Herein, we propose a novel zero-field weak parametric modulation scheme capable of ultrahigh-sensitivity extraction of longitudinal magnetic fields. Transverse modulation is employed to manifest the electron spin polarization projection induced by the longitudinal fields. Based on the perturbation model established, first-order parametric resonance associated with the longitudinal magnetic field yields significant signal enhancement under low-frequency and weak modulation conditions, while simultaneously suppressing spin-exchange relaxation caused by magnetic field modulation. We experimentally achieved a longitudinal measurement sensitivity of 16fT/Hz^{1/2}, more than an order of magnitude improved over traditional schemes, with a bandwidth of 70 Hz. Benefiting from low spin relaxation, the noise floor of the transverse magnetic field measurement is preserved at 4 fT/Hz^{1/2}. The proposed scheme pushes the boundaries of existing weak magnetic field measurement, providing critical capabilities for state-of-the-art precision experiments including new physical quantity detection.